Efecto de la época de cosecha de Maíz (Zea Mays) Amarillo Duro y su comportamiento en almacenaje en la zona del Bajo Mayo - León Rengifo, Luis Manuel (2012)
The present research aimed to determine the effect of different harvest dates on germination and quality of stored maize and quantify the weight losses during storage. The work was conducted in the facilities of the National Research Program of Maize and Rice (PNIMA) located in the EEA "El Porvenir", in the district of Juan Guerra, located in the Km 14.5 of the South Marginal Road. The experimental design was completely randomized (DCA) with factorial 2 x 5 x 4 and 4 replicates per treatment. Taking such factors under study to the Seed Protection (A1: No Phosphine, A2: With Phosphine) for days to harvest (B1: 110 days to harvest, B2: 120 days to harvest, B3: 130 days to osecha, B4: 140 days to harvest, B5: 150 days to harvest) and the evaluation days during storage (C1: 30 days of storage, C2: 60 days of storage, C3: 90 days of storage, C4: 120 days storage). The variables were evaluated at the time of harvest (grain weight and moisture content of the grains in the field) and store (moisture content of the grain to storage, germination percentage, germination rate, growth rate and total number Sitophilus sp found in storage). The conclusions were: The seeds harvested at 110, 120, 130, 140 and 150 days achieved higher growth rates relative to the root when seeds were stored 60 days harvest seed at 150, 130 and 140 had lower grain weight losses during storage when treated with chemical, a 30-day storage proved suitable for best growth results. This storage time is reflected in an increased rate of root growth, increased storage time A greater number or presence of Sitophilus sp treatments in applications that were not phosphine obtained Treatments that lower losses of stored grains were those chemical treatment, losses ranging from 2.16 Kg to 7.24 Kg per MT of grain stored, the storage humidity percentage was not affected by the effect of Phosphine in days to harvest and storage for days.